PENGAMBILAN KEPUTUSAN TRANSFER PRICING PADA PERUSAHAAN MULTINASIONAL BERDASARKAN TAX DAN EXCHANGE RATE - Suryani Cahyadi; Budi Kurniawan (Jurnal Akuntansi Bisnis, 2018)
The objective of this research is to prove, analyze the influence of tax and exchange rate on transfer pricing decision in multinational manufacturing companies. Tax is measured using a proxy ETR (Effective Tax Rate), Exchange Rate is measured using a proxy keutungan or loss transactions of companies using foreign currency, and transfer pricing was measured using dummy variables to determine the companies that conduct transactions with related parties. The analysis technique used in this research is regression analysis with the use of categorical variables logit model (Logistic Regression / Binary Choice) or also called logistic regression using EViews 9.5 program for Windows. Based on the results of logistic regression analyzes tested, testing the first hypothesis (H1) of positive influence Tax on transfer pricing decisions of companies, the result is precisely the opposite direction to that predicted, namely tax significant negative effect on the company transfer pricing decisions. While testing the second hypothesis (H2) on the effect of Exchange Rate on transfer pricing decisions the company showed a positive direction but not significant. The results of this study indicate that the tax and exchange rate does not significantly influence transfer pricing indications. The determination coefficient (McFadden R-squared) is 0.023610. This result show that 2.3%  transfer pricing is affected by tax, and exchange rate. While the rest 97.7% is explained by other variable that means many other variables in outside of tax, and exchange rate that can explain transfer pricing. Transfer pricing happen on the company with high profit purpose and using tax avoidance become the a to fulfil it, but the higher the tax rate used by the company will lower the company's transfer pricing decisions. The amount of the exchange rate (exchange rate) affects the judgment of the company, whether the company will choose to conduct transfer pricing decisions, or choose not to take a decision of transfer pricing. Keywords: tax, exchange rate, transfer pricing, multinational corporations